Legal culture and legal transplants. Apropos of the reception of the institution of precedent in the peruvian legal system - Ramírez Figueroa, Jim (2018)
The legal transplant is one of the legislative techniques most used by the legislator, so its analysis and development during its application is very important. Similarly, the use of precedents is a particular feature of various legal systems of civil law, because of this, the analysis of this institution, its foundation and its importance for the law are relevant.In this article, the author seeks to analyze and explain the development of a legal transplant in its new environment, together with the impact of various alterations in it and the conservation of it. It also seeks to analyze the function of the precedent and demonstrate that the use of it in civil law legal systems is not analogous to the powers of the legislator, but, on the contrary, rationalizes the decision making and contributes to materialize many principles and constitutional rights.